2019
DOI: 10.1002/jnr.24568
|View full text |Cite
|
Sign up to set email alerts
|

Murine maternal dietary restriction affects neural Humanin expression and cellular profile

Abstract: To understand the cellular basis for the neurodevelopmental effects of intrauterine growth restriction (IUGR), we examined the global and regional expression of various cell types within murine (Mus musculus) fetal brain. Our model employed maternal calorie restriction to 50% daily food intake from gestation day 10–19, producing IUGR offspring. Offspring had smaller head sizes with larger head:body ratios indicating a head sparing IUGR effect. IUGR fetuses at embryonic day 19 (E19) had reduced nestin (progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
1
9
0
1
Order By: Relevance
“…Our present investigation demonstrates that fetal brain serotonin concentrations are also reduced in the presence of maternal caloric-restricted IUGR. Both GLUT3 and serotonin expression may be reduced in the IUGR due to changes in progenitor cell proliferative processes that have previously been observed to result in microcephaly at E19 [51]. Similarly, in our present study, we observed a reduction in head weights consistent with microcephaly.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our present investigation demonstrates that fetal brain serotonin concentrations are also reduced in the presence of maternal caloric-restricted IUGR. Both GLUT3 and serotonin expression may be reduced in the IUGR due to changes in progenitor cell proliferative processes that have previously been observed to result in microcephaly at E19 [51]. Similarly, in our present study, we observed a reduction in head weights consistent with microcephaly.…”
Section: Discussionsupporting
confidence: 89%
“…Cerebral tissues were homogenized and sonicated in RIPA buffer (20 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1 mM Na 2 EDTA 1 mM EGTA 1% NP-40, 1% sodium deoxycholate, 2.5 mM sodium pyrophosphate, 1 mM β-glycerophosphate, 1 mM Na 3 VO 4 1 μg/mL leupeptin (Pierce, Waltham, WA, USA)) with protease inhibitors (Thermo Scientific, Canoga Park, CA, USA) including 2 mM PMSF, as previously subscribed [9, 51]. The resulting homogenate was centrifuged at 10,000 g at 4°C for 10 min, and the protein content was measured by the Bio-Rad protein assay (Bio-Rad Laboratories, Irvine, CA, USA) and subjected to Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All data extracted from the 65 studies are provided in Additional file 1 . Of these studies, 29 used Wistar rats (23 performed protein restriction [ 20 42 ] and 6 performed food restriction [ 43 48 ]), 21 used Sprague-Dawley rats (7 protein restriction [ 49 55 ] and 14 food restriction [ 56 69 ]), 3 used other strains of rats (2 protein restriction with Wistar-Kyoto [ 70 , 71 ] and 1 food restriction with Long Evans [ 72 ]) and 12 used various strains of mice (7 protein restriction [ 73 79 ] and 5 food restriction [ 80 84 ]). We therefore focused primarily on studies of Wistar and Sprague-Dawley rats.…”
Section: Resultsmentioning
confidence: 99%